THE LIMIT OF DEDUCTIVE REASONING IN LAW AND A STUDY OF NEIL MACCORMICK’S SECOND-ORDER JUSTIFICATION - Anthony U , Ezebuiro; Obiora, Remigius Mmadubugwu; Ojimba, Anthony Chimankpam (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
Among lawyers and judges, it is widely held that legal reasoning is characterized by deductive and inductive arguments. Although not many are prepared to accept this, the role of deduction and induction are not disputed. However, what is argued about is that whereas deductive reasoning holds true of factual propositions, it does not hold between norms. And even in clear cases, it is inappropriate to apply deductive reasoning; hence there is therefore, a limit to what deductive reasoning can go in law. MacCormick, for example, recognizes this limit and thus proposes a ‘second-order justification’ which, according to him, involves justifying choices; choices between rival possible rulings. These are choices to be made within the specific context of a functioning legal system. In this paper, attempt is made to demonstrate the extent to which MacCormick’s theory on ‘second-order justification’ remedies the limitation engendered in law by deductive and inductive reasoning. Taking into cognizance the fact that theoretical framework of the individual judge in question plays a huge role in the determination of court cases and judgement, the work, having presented the author’ own view, subjected same under critical interrogation, analysis and evaluation and found out that second-order justification is indeed defensible in law.